Your fyre shall burn no more : Iroquois policy toward new France and its native allies to 1701 - Brandão, José António, 1957- (University of Nebraska Press, 1997)
Why were the Iroquois unrelentingly hostile toward the French colonists and their native allies? The longstanding "Beaver War" interpretation of seventeenth-century Iroquois-French hostilities holds that the Iroquois' motives were primarily economic, aimed at controlling the profitable fur trade. Jose Antonio Brandao argues persuasively against this view. Examining the original French and English sources, Brandao has compiled a vast, unparalleled array of quantitative data about Iroquois raids and mortality rates.